The Ideological-Spiritual Foundations And Historical Conditions Of The Early Renaissance - Salamov Khurshid Bariddinovich (Genius Publishing Group, 2024)
This article analyzes the ideological and spiritual foundations of the early Renaissance, the formation of independent states in Transoxiana in the second half of the 9th century, and the development of religious and secular sciences. The views of the great scholars who emerged from Transoxiana and Khorasan, especially Khorezm and Bukhara during the early Renaissance, including Muhammad ibn Ismail al-Bukhari, are presented.
Keywords: Renaissance; enlightenment; technology